The Impact of Investment in Advancing Local Communities in Indonesia - Maharani , Anna Bella (PT. Anagata Sembagi Education, 2024)
Investment is one of the important factors in a country's economic development strategy in order to meet the needs and achieve the goals of the founding of the nation. The importance of investment for the development of the country then makes the impact and impact unavoidable by the government and local communities. In return for the profits obtained by the company from investment activities, the company has obligations or social responsibilities that must be fulfilled for the development of local communities. This is done as an effort so that the local community does not fall behind and is able to achieve progress in various fields of life.